1995
DOI: 10.1017/s1355617700000060
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific white matter degeneration following traumatic brain injury

Abstract: Morphometric analysis of magnetic resonance (MR) scans in 88 traumatic brain injury (TBI) patients demonstrated significantly larger ventricle-to-brain ratios (VBR) and temporal horn volumes, and significantly smaller fornix-to-brain ratios (FBR) and corpus callosum (CC) area measurements, compared to 73 controls. Additionally, TBI patients were grouped according to Glasgow Coma Scale (GCS) for a within-TBI sample comparison so that severity of injury on brain morphology could be examined. The severe TBI group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
1
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 141 publications
(92 citation statements)
references
References 16 publications
5
84
1
2
Order By: Relevance
“…2), which can be exploited to isolate mechanisms responsible for the recovery observed after human TBI. Clinically, cognitive function can improve after brain injury, despite reductions in brain volume [27].…”
Section: Discussionmentioning
confidence: 99%
“…2), which can be exploited to isolate mechanisms responsible for the recovery observed after human TBI. Clinically, cognitive function can improve after brain injury, despite reductions in brain volume [27].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, relatively selective atrophy of the white matter is a common neuroimaging finding years after TBI. 55 As such, there may be a very broad window of therapeutic opportunity to treat DAI spanning the acute and chronic setting. As will be discussed further, however, the exact window of opportunity in relation to specific populations of injured axons remains a matter of controversy.…”
Section: Histopathological Identification Of Daimentioning
confidence: 99%
“…Blumbergs et al (1995) in a follow-up study demonstrated that the microscopic pathology was on a continuum from mild (GCS of 13-15) to severe (GCS of 3-8), again demonstrating the susceptibility of the fornix. As shown by Viano et al (2005b), the fornix is distinctly vulnerable to the stress0strain effects of concussion and is a common area of damage in moderate-to-severe TBI, as visualized using MRI (Gale et al, 1995;Tate & Bigler, 2000;Tomaiuolo et al, 2004), where the degree of atrophy is related to severity of injury Tate & Bigler, 2000;Tomaiuolo et al, 2004;Wilde et al, 2006b). Because the fornix is a white matter structure containing projecting axons from the hippocampus, disruption in fornix integrity likely relates to the concussive effects of disrupted short-term memory, at least transiently.…”
Section: Is Brain Injury On a Continuum: Concussion R Severe Tbi?mentioning
confidence: 99%